Alih Kode Campur Kode dalam Novel Mimpi Bungsu Karya Vanny Chrisma W: Kajian Sosiolinguistik - Indrayani, Nanik (Jurnal Ilmiah Dikdaya, 2023)
Analysis of Code Switching and Code Mixing in the Novel Dreams of the Bungsu by Vanny Chrisma W Study: Sociolinguistics. Vanny Chrisma W or Fani Krismawati, born on December 4, 1983 in Sidoarjo, East Java, is the fourth of five children. Vanny Chrisma W once studied at STIE Perbanas Surabaya. Reading books is his hobby in order to increase knowledge and insight. The purpose of this study is to describe the linguistic phenomena that occur in the Dream Bungsu novel by Vanny Chrisma W, namely: (1) the form of code switching and (2) the form of code mixing. This research can be classified as a qualitative descriptive study with the research sample in the form of conversational speech in the Dream Bungsu novel by Vanny Charisma W. The sampling technique used is purposive sampling. The data collection technique used is document analysis. The results in this study indicate that the form of code switching is in the form of 11 sentences in the form of Javanese. And 6 phrases in the form of Jakarta, English, and Javanese. The next findings are, 5 words in the form of Javanese and Jakarta language. The factors causing the use of code switching and code mixing in the Dream Bungsu Novel by Vanny Chrisma W are: (1), fellow Javanese to make it easier to accept the meaning of speech from the speaker to the speech partner, (2) the Javanese who live in the village do not master the Indonesian language. , (3) the use of English to make it look prestige.